Peningkatan Keterampilan Mahasiswa melalui Pelatihan Penggunaan Aplikasi Wordwall untuk Menciptakan Pembelajaran Berbasis Gamifikasi - Ekaputra, Firdiawan (Estungkara: Jurnal Pengabdian Pendidikan Sejarah, 2025)
Advances in rapid technological advances can make digital-based learning a a breakthrough to make learning more effective. The existence of training training on the use of wordwall application can make the student participants in-depth understanding of the features available in the wordwall application, so that students' creativity in using the wordwall application can increase. Creativity in using the wordwall application can increase. The objectives of this training activity are to improve students' skills in operating media using wordwall application to create gamification-based learning. The activity training activities were given to 13 participants who were 6th semester students of the Jambi University Chemistry Education Study Program. Training activities to improve students' skills in using the wordwall application to create gamification-based learning consists of three stages of implementation, namely the first stage of preparation, the second stage of implementation, and the third stage of evaluation. Activities to improve skills through training on the use of wordwall applications to gamification-based learning that has been carried out gets extraordinary enthusiasm from the trainee students. Students experience skills in developing gamification-based learning using wordwall application. The wordwall application is easy and interesting to apply in learning, so that the trainees are interested in the activities that have been done. Participants are interested in the activities that have been